Development Of Canva Media To Improve Arabic Language Learning For Students Of University - Nunik Zuhriyah; Zakaria Firdaus; Eka Zahro’u Rosyidah; M Zunaidul Muhaimin (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to develop Canva based learning media to increase the effectiveness of Arabic language learning at University. The background of this research is based on students' needs for interactive, visual, and easily accessible media, along with the development of digital technology in education. The research method used is Research and Development (R&D) by adapting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were second semester students of the Arabic Language Education at IAI Badrus Sholeh Kediri. The learning media developed include vocabulary infographics and interactive slide presentation-based materials. The results show that Canva media is effective in improving material understanding, active student involvement in the learning process, and encouraging learning independence. Assessments from media experts and material experts show that this media is suitable for use in learning Arabic with some minor improvements. Thus, the development of Canva-based media can be an innovative solution in overcoming the boredom of conventional learning and improving the quality of Arabic language learning in university.